Fatores associados ao uso do aparelho de pressão positiva contínua nas vias aéreas em pacientes com apneia obstrutiva do sono em longo prazo - Borquez Muñoz, Pia Carolina [UNIFESP] (2017)
Objective: To identify factors associated with the long-term use of continuous positive airway pressure such as somnolence, quality of life, gender, side effects profile, variables related to sleep quality, and to titration polysomnography in adults with obstructive sleep apnea. Methods: Secondary analysis of prospective longitudinal study with patients with obstructive sleep apnea diagnosis from the Sleep Institute of São Paulo, Brazil. A total of 202 patients of either sex, with apnea-hypopnea index> 20 per hour of sleep, body mass index <40 kg / m2, without previous contact with CPAP were included. The participants underwent diagnostic and titration polysomnographies, clinical evaluation and questionnaires: Short-Form 6 Dimension Health Survey, Functional Outcomes Sleep Questionnaire, Epworth Sleepiness Scale. Follow-ups were done every 1, 6, 12, 18 and 24 months. All analyzes were performed in the statistical program IBM SPSS version 21. Descriptive data analyzed as means, standard deviations and frequencies. For associations between factors generalized linear mixed models was used. Results: The mean age of the patients was (± SD) 51.6 ± 9.4 years and the men represented 58.9% of the sample. The mean of continuous positive airway pressure use in minutes in the first month was 283.8 ± 112.3 which significantly increased after 24 months to 337.3 ± 99.9; with use rate of 78% at 24 months. The side effects associated with a lower continuous positive airway pressure use in minutes over the long term were leakage sensation (fixed effect estimator B 17.95, 95% confidence interval 0.08-35.83), difficulty exhaling (B 33.05, 95% CI 7.51, 58.59), sensation of claustrophobia (B 35.44, 95% CI 14.22 - 56.66). The most frequent side effect in patients after 24 months was upper airway dryness (45%) despite the use of the heated humidifier, however, it was not associated with a decrease in CPAP use. Also, other factors such as increased body mass index at each follow-up (B 3.85, 95% CI 1.56, 6.13), working at daytime (B 50.78, 95% CI 8.15-93.41) and being satisfied with treatment (B 37.88; 95% CI 63.91, 11.86) were related to an increase in CPAP use in minutes in the long term. With regard to polysomnography titration, percentage of oxygen saturation <90 (B 8.43, 95% CI 14.42, 2.50) and minimal oxygen saturation (B 8.29, CI 95% 13.80, 2.79) were associated with a greater use of continuous positive airway pressure at follow-up. Conclusion: Complaints reported by patients may continue over time and may not be relevant for adherence to continuous positive airway pressure treatment; however, results suggest that some factors should be followed more closely even in the long term. Increasing treatment satisfaction can help with adherence.